(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study implemented a very low frequency (VLF) data logger for monitoring the local ionosphere. The VLF data logger was built around a Raspberry Pi 3B+. A 1 m2 loop antenna with a sensitivity of 5.86 × 10-4 V/s1/2m-1 was built to receive the VLF signal. The system recorded three frequencies: 19.2, 19.58, and 19.8 kHz from South Vijayanarayanam (India), Anthorn (UK), and Exmouth (Australia), respectively, at Ibadan, Nigeria. Three months (June–August 2019) of data were reported in this study. The results revealed that the data logger saves up to 83% energy compared to an average laptop. The system was able to characterize the diurnal morphology of the D-layer. The diurnal morphology shows the sunrise and the sunset effect (signature). It was noted that variations exist in the aver age signal strength on quiet days; therefore, further study is recommended to investigate the geophysical conditions that are responsible for these variations.